The Use of Generative AI in Designing Adaptive Digital Learning Materials: A Literature Review - Baiq Anisya Nelahi Purnadya; Baiq Oriza Januarlinda; Nurul Asmaya Fitria Hasanah; Nina Nisrina; Gunawan Gunawan (Indonesian, 2024)
The development of generative Artificial Intelligence (AI) provides new opportunities in designing adaptive digital learning materials through automated content generation and personalized learning. This study aims to examine the roles, potentials, and challenges of generative AI in developing adaptive digital learning materials. The method used is a literature review of 15 scientific articles published between 2015-2024, retrieved from Google Scholar and Publish or Perish. The results indicate that generative AI supports automated content creation, personalization based on learners’ needs, and real-time material delivery. These capabilities enhance learning effectiveness, flexibility, and relevance. However, challenges remain, including teachers’ readiness, unequal access to technology, and the potential decline in students’ independent learning. Therefore, the integration of generative AI needs to be implemented carefully to optimally support adaptive digital learning.